An overview of child psychology in the Philippines.[article]. - Ventura, Elizabeth R.
A review of 144 studies done in the area of Child Psychology from the late sixties up to 1980 was made. Trends across all the studies were looked for in terms of the following categories: age and sex of subjects, the locale of the study (rural or urban), methods used, and the areas of development covered. It was found that most of the students dealt with sex differentials, were done in urban settings, involved in one-session designs, made use of tests, and dealt with the socio-emotional development of children. On the basis of the findings, recommendations were made regarding the possible focus of future researches. The need for child psychologists to be more involved in defining and conceptualizing researches, as well as in applying research findings to existing situations, was also pointed out.